IMPLEMENTATION OF SERIES TYPE HYBRID ELECTRIC VEHICLE SIMULATOR TO IMPROVE STUDENT LEARNING OUTCOMES (Universitas Pendidikan Indonesia, 2024)
The background of this research is the lack of students' understanding of knowledge, analysis, and diagnosis of hybrid vehicle damage that is good and clear in the Hybrid Vehicle Technology course. There are several factors that influence the difficulty of student understanding, the results of observations and interviews with the lecturer, one of the influences is the lack of learning media in the form of real objects because during the learning only use media in the form of text and images. The use of interactive simulator or real object learning media is one effort to overcome this problem. The purpose of this study is to determine the increase in learning outcomes after using the Series Type Hybrid Electric Vehicle simulator in the Hybrid Vehicle Technology course. The research method used is quantitative and the research design used is Pre-Experimental Design with a One-Group Pretest-Posttest Design. The research sample is 20 students of grade A who contracted Hybrid Vehicle Technology, taken by purposive sampling. The results showed that the average post-test value was greater than the pre-test. Based on the results of the paired sample t-test, it shows that there is an increase in learning outcomes, the increase is measured using the n-gain test with a moderate category after using the series type hybrid electric vehicle simulator in the Hybrid Vehicle Technology course.Penelitian yang berlatar belakang karena kurangnya nilai dari pemahaman mahasiswa terkait pengetahuan, analisis, dan diagnosa kerusakan kendaraan hybrid yang baik dan jelas pada mata kuliah Teknologi Kendaraan Hybrid. Terdapat beberapa faktor pengaruh sulitnya pemahaman mahasiswa, hasil observasi dan wawancara kepada dosen pengampu salah satu pengaruhnya yaitu kurangnya media pembelajaran berupa benda nyata karena pada saat pembelajaran hanya memanfaatkan media berupa teks dan gambar saja. Penggunaan media pembelajaran simulator atau benda nyata yang interaktif menjadi salah satu upaya dalam mengatasi permasalahan tersebut. Tujuan dari penelitian ini yaitu untuk mengetahui peningkatan hasil belajar setelah menggunakan simulator Series Type Hybrid Electric Vehicle pada mata kuliah Teknologi Kendaraan Hybrid. Metode penelitian yang digunakan yaitu kuantitatif dan desain penelitian yang digunakan adalah Pre-Experimental Design dengan bentuk One-Group Pretest-Posttest Design. Sampel penelitian yaitu mahasiswa tingkat 3 kelas A yang mengontrak Teknologi Kendaraan Hybrid sebanyak 20 mahasiswa yang diambil secara purposive sampling. Hasil penelitian menunjukkan nilai rata-rata post-test lebih besar dari pre-test. Berdasarkan hasil uji paired sample t-test menunjukkan bahwa terdapat peningkatan hasil belajar, peningkatannya diukur menggunakan uji n-gain dengan kategori sedang setelah menggunakan simulator series type hybrid electric vehicle pada mata kuliah Teknologi Kendaraan Hybrid